The Level of Speaking Skills Among Students in the Faculty of Humanities and Islamic Sciences at Prince Songkla University, Pattani Campus - Panprae, Prasert; Taher, Rusdee; Binmong, Sorhibulbahree; Wateh, Yasir (MENARA : Journal of Islamic and Contemporary Issues, 2025)
The level of speaking skill among the students at the Faculty of Humanities and Social Sciences and the Faculty of Islamic Sciences at Pattani Campus shows a noticeable discrepancy between strengths and weaknesses. Therefore, this study aimed to identify the levels of students’ speaking proficiency, their mastery of speaking skills, and the positive and negative factors that influence the acquisition of speaking skills. The study employed a descriptive-analytical approach by obtaining and analyzing the data, making comparisons, and drawing conclusions. Data were collected through a questionnaire administered to a sample of 60 students from the two faculties, covering all levels from first to fourth year. The study found that first-year students from both faculties were at the beginner level, while second, third, and fourth-year students were at the intermediate level. One of the key recommendations is to organize intensive courses for third and fourth-year students and to increase the number of relevant courses and language rooms.